The Effectiveness of Smart City Implementation Through the TransJogja Application - Raihan, Zidan Achmad; Fadhilah, Muhammad; Aprianto, Rizal (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The implementation of the smart city concept in Yogyakarta is realized through the development of digital based public transportation services, one of which is the Trans Jogja application. This study aims to evaluate the effectiveness of the Trans Jogja application in supporting urban mobility and improving the quality of public transportation services. Using a descriptive qualitative approach, data were obtained through interviews, field observations, and document analysis. The findings indicate that the Trans Jogja application plays a significant role in enhancing the accessibility, efficiency, and convenience of bus services by providing real-time information, intermodal integration, and digital payment systems. However, several challenges remain, such as underutilized routes, discrepancies in travel time estimations, and the need to improve bus stop facilities. The study recommends the development of application features, improvement of supporting infrastructure, and public education to encourage a shift from private vehicles to public transportation. These efforts represent a strategic step toward realizing inclusive, efficient, and sustainable mobility in Yogyakarta as a smart city.